A cross-sectional study of mental health and suicidality among trans women in São Paulo, Brazil - Reis, Arianne; Sperandei, Sandro; de Carvalho, Paula Galdino Cardin; Pinheiro, Thiago Félix; de Moura, Ferdinando Diniz; Gomez, José Luis; Porchat, Patrícia [UNESP]; Bastos, Francisco Inácio; McFarland, Willi; Wilson, Erin C.; Veras, Maria Amélia (Springer Nature, 2021)
Background: Trans women have been shown to experience disproportionately poor outcomes in physical and mental health. Although it is common to talk about the violence against trans people, little is still known about mental health outcomes and experiences of suicidality among trans women, particularly in developing countries. This study aims to investigate risk factors and associations with mental health, suicide ideation and suicide attempts among trans women in the largest metropolitan area in Brazil. Methods: Trans women living in São Paulo were recruited between May 2017 and July 2019 using the long-chain peer referral method Respondent-Driven Sampling. Multivariate regression models were used to investigate the associations with K10 score classification (logistic) and suicidal ideation/suicide attempt (ordinal logistic). Results: A total of 763 trans women were included in the study. Over one quarter (26.5%) of trans women had been diagnosed with anxiety in the past, and close to one in five (19.1%) trans women had received a diagnosis of depression. More than two in five (41.9%) trans women had moderate to severe psychological distress. More than half of all participating trans women reported having previously either experienced suicidal ideation or attempted to take their own lives (25.0 and 31.2% respectively). In multivariate regression, moderate to severe psychological distress was associated with homelessness, income, current sex work, use of stimulant drugs, history of physical abuse, depression diagnosis and access to mental health treatment. Suicidal ideation and suicide attempts were associated with race/skin color, living arrangements, marital status, current sex work, history of sexual violence, depression and PTSD diagnoses, access to mental health treatment and psychological distress. Conclusions: This study showed that there is a significant association between mental health conditions, lack of treatment for these conditions and suicidality among trans gender women. Findings point to the need for a structural transformation in Brazil that enables a reduction in the social inequality and violence that impact the mental health of trans women. A number of recommendations to achieve this are provided.
Keywords: Mental health; Risk factors; Suicidal ideation; Suicide attempt; Transgender women